(untitled) (Global Journal of Medical Research, 2017)
Copper plays important role of cancer cell progression and development, malignant cell growth, and angiogenesis in invasive and metastatic growths. Specially, angiogenesis and autophagy have been worthy of new blood vessel formations and fusion proteins respectively for malignant and tumor cell growths. Schiff base copper(Ⅱ) complexes have anti-proliferative activity against cancer cells. Cu 2+ ions play an important role as pro-cancer factor in tumor tissues especially in tumor angiogenesis, invasion, and metastasis.Specially, Cu 2+ ions as Cu-chelating complex can inhibit formation of new blood vessel of tumor cell against angiogenesis in cancer.Promotion and development of cancer tissues have been proceeding with homeostatic imbalances of copper, in which can be caused by the uptake of excessive amounts of copper and some genetic defects.Cancer cell killing via ROS that superoxide anion O 2 -, hydroxyl radical ･OH, hydrogen peroxide H 2 O 2 mainly may be performed under cellular Cu 2+ ions induced ROS generations in tumor cells. Finally, Cu 2+ -H 2 O 2 induced DNA base-pairs inhibition can be regarded as being undergone to DNA damages due to Cu 2+ -complex formations within DNA base-pairs G≡C, A=T by Cu 2+ substitutions in hydrogen bonds of DNA base-pairs.